SAE Technical Paper Series 2015
DOI: 10.4271/2015-01-1369
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Walled Compliant Mechanism Component Design Assisted by Machine Learning and Multiple Surrogates

Abstract: This work introduces a new design algorithm to optimize progressively folding thin-walled structures and in order to improve automotive crashworthiness. The proposed design algorithm is composed of three stages: conceptual thickness distribution, design parameterization, and multi-objective design optimization. The conceptual thickness distribution stage generates an innovative design using a novel one-iteration compliant mechanism approach that triggers progressive folding even on irregular structures under o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…While more research is needed, the parametric studies in this work show that the analysis (crash simulation) of the cluster designs is a suitable indicator to approximate the optimal number of clusters. Other approaches such as the elbow method, information criterion approach, and the Silhouette method [51] are computationally less expensive but not as effective as the parametric study shown in this work. Ongoing investigation aims to control the structural complexity of the clustered design generated by the proposed approach.…”
Section: Mechanical Compliance Under a Static Loadmentioning
confidence: 82%
See 2 more Smart Citations
“…While more research is needed, the parametric studies in this work show that the analysis (crash simulation) of the cluster designs is a suitable indicator to approximate the optimal number of clusters. Other approaches such as the elbow method, information criterion approach, and the Silhouette method [51] are computationally less expensive but not as effective as the parametric study shown in this work. Ongoing investigation aims to control the structural complexity of the clustered design generated by the proposed approach.…”
Section: Mechanical Compliance Under a Static Loadmentioning
confidence: 82%
“…As an alternative, metamodels can be derived by sampling the dynamic, nonlinear finite element model. The resulting metamodels are numerically inexpensive and allow to find nearoptimal solutions through the use of global multi-objective algorithms [51]. The key aspect to using metamodels for global optimization lies in balancing between global exploration and local exploitation.…”
Section: Generation Of the Initial Metamodelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The input observations to the cluster analysis algorithm is the conceptual material distribution x * ∈ R n and the desired number of clusters K, where 1 K n; usually, K n (Algorithm 1 [32]). A discussion on the optimal value of K can be found in [33].…”
Section: Clustering (Step 2)mentioning
confidence: 99%
“…In other words, it is desirable to generate an accurate metamodel that explores a large portion of the design space with a few sampling points [34]. Several metamodels have been evaluated for design problems in crashworthiness, including: polynomial response surface, radial basis functions, and Kriging [33]. Based on cross-validation errors, Kriging is the preferred metamodel and it is used in this work.…”
Section: Metamodel-based Global Optimization (Step 3)mentioning
confidence: 99%